Enhancing flood risk maps by a participatory and collaborative design process. (November 2020) - Minucci, G.; Molinari, D.; Gemini, G.; Pezzoli, S.
Abstract: The European Floods Directive (2007/60/EC) requires Member States to make flood hazard and risk maps available to the public. Yet, making flood risk maps available is not enough to inform the public about risk, they need to be understood correctly. Which are the elements that make risk maps suitable and clear for non-expert citizens? Which is the information expected by local technicians in flood risk maps? In order to answer to these questions, co-mapping labs were organized within the project "Flood-IMPAT+: an integrated meso- & micro-scale procedure to assess territorial flood risk" in the city of Lodi, Northern Italy. The co-mapping labs involved representatives of the civil society, economic activities and local institutions responsible for flood risk management. They were asked to examine flood maps developed within the project with respect to their components of hazard, exposure, vulnerability and damage in order to collect guidelines for increasing communicative effectiveness of the maps. Contributes from participants were fundamental to understand the type of information and language that make flood risk successfully represented for and understood by different end-users. Currently, the same maps provided in flood risk management plans are consulted by those who are involved in planning processes, emergency overcoming, risk mitigation or simply exposed to risk. On the contrary, co-mapping labs highlighted the need to produce maps calibrated on stakeholders' needs, i.e. which supply different information according to the map final use. In this regard, the effectiveness of the tool map itself was questioned and the request for a mix of tools combining hard copies of the maps and Information Systems allowing the combination and the query of interchangeable layers of information arose. In addition, the labs underlined the need to enhance the governance between the actors responsible for flood risk management as well as the need of the public and the civil society of being involved in the flood mapping process and supported in their understanding. In conclusion, the co-mapping labs had the added value to be an experience of collaborative inquiry and participatory design in flood risk communication, supplying suggestions and recommendations that should be incorporated in the design of novel flood hazard and risk maps.